2008
DOI: 10.1194/jlr.m700328-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated fatty acid supplementation reverses stress-induced modifications on brain monoamine levels in mice

Abstract: The aim of this study was to examine the effects of supplementation with n-3 polyunsaturated fatty acids (PUFAs) on stress responses in mice subjected to an unpredictable chronic mild stress (UCMS) procedure. Stressinduced modifications in coat and aggressiveness were evaluated, and phospholipid PUFA profiles and monoamine levels were analyzed in the frontal cortex, hippocampus, and striatum. The results showed that repeated exposure to mild stressors induced degradation in the physical state of the coat, lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 50 publications
4
60
0
1
Order By: Relevance
“…The effects of stress on body weight are still controversial. Although various studies indicated a decrease in body weight [31,32], some recent studies showed no change [33,34]. In our model, KXS could reverse the LV-shBDNF-induced weight loss, which is similar to our previous study in the CMS model [12,29].…”
Section: Discussionsupporting
confidence: 80%
“…The effects of stress on body weight are still controversial. Although various studies indicated a decrease in body weight [31,32], some recent studies showed no change [33,34]. In our model, KXS could reverse the LV-shBDNF-induced weight loss, which is similar to our previous study in the CMS model [12,29].…”
Section: Discussionsupporting
confidence: 80%
“…This is confirmed by the fact that NOS inhibition modulates central serotonin release (Kiss, 2000;Smith&Whitton, 2000;Wegener et al, 2000). In rats exposed to chronic mild stress, 5-HT and 5-HIAA (5-hydroxy indol acetic acid) levels decreased significantly in many brain regions, compared to nonstressed animals (Li et al, 2003;Vancassel et al, 2008). Therefore, it can be the fact that effects of TRIM might be explained by its ability to reverse the UCMS-induced alteration of 5-HT. )…”
Section: Effects Of Nos Inhibitors In Depressionmentioning
confidence: 56%
“…Indeed, many studies have reported abnormalities of biogenic amines and of their metabolites in blood, urine, and CSF in depressed patients (Mann et al 1992;Ruhe et al 2007) and in rodents (Torres et al 2002;Elhwugei 2004). Recently, Vancassel et al 2008 also showed that the UCMS regimen induced modifications on brain monoamine level in mice. The previous study and our results showing the changes in monoamines levels induced by UCMS regimen reinforce the construct validity of this model.…”
Section: Discussionmentioning
confidence: 97%